2018
DOI: 10.1007/s00285-018-1238-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimating intratumoral heterogeneity from spatiotemporal data

Abstract: Glioblastoma multiforme (GBM) is a malignant brain cancer with a tendency to both migrate and proliferate. We propose modeling GBM with heterogeneity in cell phenotypes using a random differential equation version of the reaction-diffusion equation, where the parameters describing diffusion (D) and proliferation ([Formula: see text]) are random variables. We investigate the ability to perform the inverse problem to recover the probability distributions of D and [Formula: see text] using the Prohorov metric, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…This case is going to be investigated in a forthcoming paper. Moreover, there have been a plethora of studies trying to quantify intratumoral heterogeneity, see [33][34][35][36], nevertheless our method is able to include the existing literature and analyze the impact of data-driven heterogeneity distribution in more realistic tumor models. For instance, data regarding the invasive behavior heterogeneity, e.g., migration speed distribution, of tumor cells can be easily integrated and analyzed from our framework, such as in [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case is going to be investigated in a forthcoming paper. Moreover, there have been a plethora of studies trying to quantify intratumoral heterogeneity, see [33][34][35][36], nevertheless our method is able to include the existing literature and analyze the impact of data-driven heterogeneity distribution in more realistic tumor models. For instance, data regarding the invasive behavior heterogeneity, e.g., migration speed distribution, of tumor cells can be easily integrated and analyzed from our framework, such as in [37].…”
Section: Discussionmentioning
confidence: 99%
“…We consider ω ∈ Ω, where Ω is introduced in Remark 4. Now (35) entails that for any fixed ω ∈ Ω, fixed 2n , there exists Nk (ω) such that for each N > Nk (ω)…”
Section: The Novel Averaging Principlementioning
confidence: 99%
“…However, the assumption of white noise is the worst possible scenario related to tumor heterogeneity, and therefore other noise distributions should be analyzed such as Gaussian noise. Moreover, there have been a plethora of studies trying to quantify intratumoral heterogeneity, see, 1,20,22,24 nevertheless our method is able to include the existing literature and analyze the impact of data-driven heterogeneity distribution in more realistic tumor models. Furthermore, our method can be also implemented to investigate the long-time dynamics of the full GoG system (5.1)-(5.2), which will be the subject of a forthcoming work.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have shown that the Fisher-KPP equation is clinically relevant [56,39,4], the model assumes an intratumor homogeneous cellular behavior that might not be true in GBM populations [48]. As a result, many PDE models have been introduced to account for the population heterogeneity in GBM populations [48,30,35,42,2,50,17,44,54,40].…”
Section: Introductionmentioning
confidence: 99%